1990
DOI: 10.1055/s-0038-1647321
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Thromboxane Receptor Blocking Drug, AH23848, Reduces Platelet Deposition on Vascular Grafts in Man

Abstract: SummaryThe antithrombotic effect of a specific thromboxane A2 receptor blocking drug, AH23848, on radio-labelled platelet deposition in mature Dacron aorto-bifemoral grafts has been evaluated in patients. Thirty patients were randomly allocated to AH23848 70 mg, aspirin 300 mg plus dipyridamole 75 mg or placebo 8-hourly for 9 days. AH23848 inhibited platelet aggregarion induced by the thromboxane ,A2 mimetic U-46619; no such effect was observed with aspirin plus dipyridamole. 111In-platelet uptake was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Aspirin, which acetylates cyclo-oxygenase and so prevents TxA2 synthesis by platelets (21), has no measurable effect on platelet deposition in a similar model of acute arterial thrombosis (22). Our results, and those of others using different approaches (10,11,24,25) strongly suggest that receptor blockade may be a more effective strategy of treating arterial thrombosis than inhibition of This assumption is further supported by the variable success that was achieved with TxA2-synthetase antagonists (2,25). Aspirin prevents the synthesis of both the prostaglandin derived agonists (TxA2, cyclic peroxides) and antagonists (prostaglandin D) by platelets (24,26).When the TxA2-blockers are used, the proaggregatory effect of TxA2 and the cyclic peroxides on platelets is blocked, while inhibition of platelet function by prostaglandin D2…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Aspirin, which acetylates cyclo-oxygenase and so prevents TxA2 synthesis by platelets (21), has no measurable effect on platelet deposition in a similar model of acute arterial thrombosis (22). Our results, and those of others using different approaches (10,11,24,25) strongly suggest that receptor blockade may be a more effective strategy of treating arterial thrombosis than inhibition of This assumption is further supported by the variable success that was achieved with TxA2-synthetase antagonists (2,25). Aspirin prevents the synthesis of both the prostaglandin derived agonists (TxA2, cyclic peroxides) and antagonists (prostaglandin D) by platelets (24,26).When the TxA2-blockers are used, the proaggregatory effect of TxA2 and the cyclic peroxides on platelets is blocked, while inhibition of platelet function by prostaglandin D2…”
Section: Discussionsupporting
confidence: 89%
“…Our results nevertheless compare favourably with the results obtained in studies where other TxA2-antagonists were used. These antagonists inhibited platelet deposition on Dacron vascular grafts in hum ans (24), and improved graft patency in dogs (25) (Table 2) were affected. The lower dosage which was used may explain why platelet deposition and accumulation of additional platelets onto the preformed thrombus were only partially inhibited, since both thrombin formation and the effect of ADP on platelets were not affected.…”
Section: In Vitro Platelet Aggregationmentioning
confidence: 99%
“…Lane et al demonstrated the involvement of thromboxane A 2 in the process of platelet deposition onto Dacron grafts. 63 They administered AH23848, a thromboxane A 2 receptor antagonist, into patients with aortobifemoral grafts for 9 days and compared its effects on platelet deposition to those of aspirin and dipyridamole. Using 111-Indium-labeled platelets, the thrombogenicity index (TI; a daily measure of the rate of graft platelet accumulation) was measured in each group arm.…”
Section: Reviewmentioning
confidence: 99%
“…Patients treated with systemic AH23848 demonstrated significantly reduced TIs compared to the other group arms (0.115 vs 0.193 placebo vs 0.175 aspirin and dipyridamole). 63 In a randomized controlled clinical trial, Pieters et al used another thromboxane A2 receptor antagonist, Bay u3405, to investigate 111-Indium labeled-platelet deposition onto implanted Dacron aortic grafts. Gamma-camera imaging demonstrated a reduction in platelet graft deposition and a reduced TI in patients treated systemically for 7 days with Bay u3405.…”
Section: Reviewmentioning
confidence: 99%
“…In the late 1980s, AH23848 has been widely studied in a number of laboratories and has been shown to be a selective TXRA. Nevertheless, despite its promising antithrombotic properties revealed in man [56], AH23848 was found to be teratogenic and its development discontinued [57]. A closely related analogue, GR 32191 (vapiprost, 29), bearing a PGF 2α ring, has been demonstrated to be a more potent and specific TXRA than AH23848 [58].…”
Section: Prostanoid Txa 2 Receptor Antagonistsmentioning
confidence: 99%